Social Media and Political Participation: A Systematic Literature Review and Bibliometric Analysis - Intje Supriadi Indama; Andi Hartati; Anies Handayani; Siska Siska; Budianto Taib (Sean Institute, 2026)
Social media has become a central arena for political communication, participation, and the formation of digital public opinion, while social media influencers increasingly operate as political intermediaries. This study maps the development, intellectual structure, and thematic direction of research on social media and political participation. A bibliometric analysis and systematic literature review were conducted using 107 unique Scopus records published between 2020 and July 2026. All records were used for performance and science-mapping analysis, while 80 English-language journal articles and reviews formed the qualitative synthesis corpus. The dataset comprised 95 publication sources, 239 authors, 44 countries, and 1,001 citations. Publication output increased from five documents in 2020 to 35 in 2025, indicating rapid consolidation of the field. Keyword co-occurrence analysis produced 27 interconnected terms, 70 links, and three major clusters: social media, elections, and informational risks; political influencers, platforms, and democracy; and youth political participation, efficacy, and digital activism. The literature consistently identifies influencers as accessible opinion leaders who can stimulate political interest and online engagement, but evidence on sustained offline participation remains conditional. Recent research increasingly focuses on TikTok, Generation Z, artificial intelligence, misinformation correction, and regulatory accountability. The study concludes that future research should prioritize longitudinal and experimental designs, comparative Global South settings, platform algorithms, political disclosure rules, and the distinction between passive exposure, expressive engagement, and durable civic participation.